Taekwondo - Ingram, R.; McLaughlin; Radcliffe, Y. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Modern elite Taekwondo is incredibly competitive and demanding for those athletes that are involved. With a minimum of 5 high scoring competitions a year and numerous other oppor- tunities to score ranking points, the athletes need to be close to their physical peak throughout, for several years, building towards an Olympic Games. The fights themselves are becoming more and more physical as athletes become more professional in their training methods and the rules increase the requirement for those athletes to operate at the outer ranges of motion in order to score big. In the authors` experience, athletes that focus early on in their careers on quality training practises that prioritise movement competency and functional mobility, with special attention given to the hip complex, are the athletes most likely to optimise their training and competition time. Once these areas are addressed, a quality and progressive approach to strength and power development, balanced against the athlete`s technical development, can strongly support the athlete`s performance in competition. There is a huge amount of research needed into the sport and its recent rule changes in order to establish objective performance indicators for athletes to strive for; however, in the authors` experience the most successful and highest performing Taekwondo fighters have also been extremely competent in the S&C train- ing environment, supporting the value of these training methods and their place in the athlete`s training schedule.